Phyto-Pharmacognostic Evaluation of Strobilanthes Barbatus Nees - Sreelakshmi C. N; Jayanthi C. K (AYUSHDHARA, 2022)
Dravyaguna forms the backbone of rational therapeutics. Correct and skillful application of drugs is impossible without proper understanding of its identification and pharmacology. Strobilanthes barbatus Nees shows a wide distribution in Kerala. This drug is popular among the traditional healers and local people for its diverse clinical application. Till now no major research works have been done on its efficacy regarding the Ayurvedic perspectives. Methodology: Pharmacognostic analysis was conducted at the Department of Dravyaguna Vijnanam, Mannam Ayurveda Co-operative Medical College, Pandalam. Aerial part of Strobilanthes barbatus Nees was macroscopically and microscopically evaluted. The powder characteristrics of the dried sample was also analysed. Result and Discussion: Bearded Coneflower is a gregarious shrub, 3-4 m tall, sometimes climbing.Macroscopic analysis: stem is rectangular in outline, with a lamina like wing structure projecting from four angles. Leaf is simple, petiolate, oppositely arranged in unequal pairs, elliptic-lance shaped. Conclusion: The current study drug shares similar morphological features to that of S. ciliatus. Strobilanthes barbatus could be easily propagated and cultivated. It is endemic to Western Ghats and widely distributed in Kerala.